On time-dependent reliability of sustainable structures - Juocevicius, V.; Kudzys, A. (Видавництво Національного університету «Львівська політехніка», 2007)
Peculiarities of sustainable reliability predictions for load-carrying structures of buildings, construction and civil engineering works are discussed. The quantitative probabilistic parameters of the structural safety and durability of members and their systems are formulated and applied. A new strategy for probability-based quality predictions of sustainable structures is presented. The safety prediction is meant for particular members (sections, connections) exposed to action effects. Contrary to this prediction, the durability issues for whole structural members (slabs, beams, columns, walls) as auto-systems representing their multi-criteria failure mode are considered. The methods of conventional resistance and transformed conditional probability design in practical calculations of reliability parameters of sustainable structures and works are presented. It is recommended to calibrate the target reliability index of sustainable structures considering not only the consequences of failure of the members but also their functional working classes.